2023
DOI: 10.3390/su15065336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Natural Hazards on Agricultural Production Decision Making of Peasant Households: On the Basis of the Micro Survey Data of Hunan Province

Abstract: The agricultural production decision making of peasant households can have a direct impact on agricultural development trends and national food security, and the impact of natural hazards on the agricultural production decision making of peasant households merits significant consideration. On the basis of the micro survey data of Hunan Province in 2022, this paper empirically discusses the impact of natural hazards on peasant households’ agricultural production decision making by using a Probit model. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Building on existing research (Yang et al, 2023;Zhang et al, 2022), this paper presents different types of score matching estimators, including Kernel matching, local linear matching, radius matching, and nearest neighbor matching (k = 1, k = 4). Table 5 presents the impact of saline intrusion on household income, obtained using the propensity score matching method.…”
Section: Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on existing research (Yang et al, 2023;Zhang et al, 2022), this paper presents different types of score matching estimators, including Kernel matching, local linear matching, radius matching, and nearest neighbor matching (k = 1, k = 4). Table 5 presents the impact of saline intrusion on household income, obtained using the propensity score matching method.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Estimate by propensity score matching methodThe study sample may have endogenous selection problems because households choose their place of residence according to the natural environment, climate, and soil characteristics. Referring to existing research(Yang, Xu, Xie, Sohail, & Gong, 2023;Zhang et al, 2022), we used propensity score matching (PSM) to reduce this source of bias. We use a dummy variable equal to 1 if the household regularly suffers from saline intrusion at 4 g/l (treatment group) or 0 otherwise (control group).…”
mentioning
confidence: 99%
“…As a result, many scholars have conducted research on the cultivation of environmental talents, and some scholars have studied the role of human capital in green growth and environmental performance, which has shown that increased investment in human capital can promote green economic growth and realize environmental protection [47]. Yang et al [48] empirically analyzed the impact of natural disasters on agricultural production decisions using the probit model. The results of this study can provide empirical evidence for the government to formulate relevant policies.…”
Section: Introductionmentioning
confidence: 99%